The Triple Bottom Line In Procurement And Contracting - A Pathway To A Sustainable And Profitable Business Model - Imonioro, Ejayita (Cranfield University, 2025)
Procurement is a strategic arena in which the triple bottom line (TBL), comprising economic, environmental, and social performance, is embedded and contested. This thesis systematically examines how TBL dimensions are integrated into procurement and contracting, and how these practices contribute to the development of sustainable and profitable business models. While the review spans multiple industries, the oil and gas (O&G) sector, particularly in Nigeria and comparable economies, is the focal point, given its high risks and institutional complexity. A systematic literature review covering 2015–2025 was conducted across four databases and grey literature, with librarian support and snowballing . Sources were screened and appraised using consistent criteria, classified into three tiers, and analysed with a data extraction framework. The findings highlight five key dynamics that shape procurement. Governing stakeholder influence is exercised through regulation, fiscal levers, international standards, and community expectations; however, fragmented enforcement limits its effectiveness. Managing trade-offs remains a challenge, as lowest-price logics dominate; still, LCC and multi-criteria evaluation demonstrate how resilience and competitiveness can align with sustainability. Collaboration and inclusivity provide opportunities for progress. Supplier development, partnerships, and local content foster innovation and community benefits, although smaller firms often face capability gaps and dependency risks. Tools such as decision-support models, traceability mechanisms, and digital platforms provide evidence-based pathways to sustainable procurement but are constrained by measurement gaps and resource limitations. Ethical accountability, expressed through compliance clauses, transparency, and audits, is also important; however, inconsistent monitoring reduces its impact. The study reframes procurement as a contested space where TBL principles are negotiated, extending stakeholder and sustainable supply chain theories to contexts with weak governance. Managerially, it highlights enforceable iii contracts, long-term evaluative tools, supplier capability building, and inclusive digitalisation. Future research should deepen analysis of O&G procurement in Africa, assess emerging technologies, and address the underdeveloped social pillar of sustainability.
Keywords: Oil and Gas Industry; Nigeria; Supply Chain Management; Value Creation; Lifecycle Costing; Ethical Accountability